FAKTOR INTERNAL DAN EXTERNAL YANG MEMPENGARUHI AUDIT DELAY DAN TIMELINESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lia Permatasari (Universitas Katolik Soegijapranata Semarang, 2012)
Timeliness and audit delay in financial reporting is a significant characteristic of accounting information. Stale information is of little use to investors in their investment decision-making processes. Undue delay in releasing financial statements increases uncertainty associated with investment decisions. Therefore, the objective of this research is to investigate the influence of intern factor such as firm size, firm age, firm status, subsidiaries, existence of internal audit division, profitability, solvability, total asset turn over, extraordinary items and the extern factor such as public accountant size, public accountant age, auditor opinion toward the audit delay and timeliness on manufacture companies that listed in Indonesia Stock Exchange for the period 2006-2008. The hypothesis purpose were tested by multiple linier regression models. The result shows subsidiaries, existence of internal audit division and opinion auditor have influence on timeliness and audit delay. On the other hand, firm size, firm age, public accountant size have influence on timeliness and public accountant age have influence on audit delay